Tragedy in Paracambi-RJ: Analysis of the impacts of floods and floods from the perspective of mental health, infectious diseases, absence of socio-environmental intervention and public health in the scenario before and after flooding - Teixeira, Jeferson Manoel; Monteiro, Tiago da Cruz; Souza, Luis Henrique Brito Barreto; de Figueiredo, Wenberger Lanza Daniel; Barbosa, Erick Matheus Garcia; de Araújo, Valdete Santos (Seven Editora, 2024)
The city of Paracambi-RJ, developed along the Rio dos Macacos, a region susceptible to flooding. With a population of 41,375, inadequate infrastructure and lack of effective drainage increase the municipality’s vulnerability to flooding. In February 2024, Paracambi faced one of the largest floods in recent years, exacerbated by the lack of warning systems and proper river management. Poor infrastructure, coupled with inefficient prevention measures, has aggravated outbreaks of infectious diseases such as Dengue, Chikungunya, Leptospirosis and diarrheal diseases. The need for an in-depth analysis of the impacts and responses of public authorities becomes crucial. The study seeks to analyze the causes and consequences of floods in Paracambi, evaluating the actions of local authorities and the measures adopted to mitigate these disasters. In addition, it is intended to review the global scientific literature on the relationship between floods and public health, correlating data on disease notifications with water quality in the municipality. The public health impacts of floods are vast and multifaceted, including communicable diseases, mental health problems, and direct physical harm. Underreporting of diseases and the lack of an efficient management system are significant barriers to mitigating impacts. The floods in Paracambi underscore the urgent need for improvements in drainage infrastructure and more effective urban planning. It is imperative that municipal management implement measures for prevention, health education and control of zoonoses. Strengthening epidemiological surveillance and continuous training of health workers are essential to prevent future catastrophes and protect public health. DOI:https://doi.org/10.56238/sevened2024.016-014